Public Speaking: Several Essential Challenges - Zainul Aminin; Kusumarasdyati Kusumarasdyati; Nur Fauzia; Abdur Rosyid (Universitas Muhammadiyah Prof. DR. HAMKA, 2022)
Oral communication in front of an audience is known as public speaking, a combination of speaking skills and the art of speaking. Speaking in front of an audience involves more than just getting your point out; it also involves considering how well it will be received and accepted into the hearts of the audience. Learning public speaking has its own challenges. The purpose of this study is to identify the challenges faced by students in learning public speaking. It is a descriptive qualitative study with 13 participants from an English Language Education Study Program in Surabaya. Purposive sampling was used to obtain the participants. Two instruments are needed to collect data in this study: a questionnaire and an interview. The results of the study show that the challenges faced by students, in general, include two things, namely internal and external challenges. Internal challenges include psychological conditions, language competence (vocabulary mastery, fluency, and pronunciation), and topical knowledge, while external challenges are performance conditions and learning environment. Keyword: public speaking, challenges